Risk Factors Related to Obstructive Sleep Apnea Syndrome in Children with Repaired Cleft Lip and Palate - Posiri, Chinnakrij; Chaiworawitkul , Marasri (Thai Journal of Orthodontics, 2024)
Obstructive sleep apnea syndrome (OSAS) is a common sleep-related breathing disorder frequently detected in children, especially when a craniofacial condition such as cleft lip and palate (CLP) plays a role. Their distinct craniofacial alterations, marked by a diminished midface and a retrusive maxilla compared to non-cleft children, increase the susceptibility of children with CLP to OSAS. These anatomical changes result in a decreased cross-sectional airway volume, increasing the likelihood of OSAS development in children with CLP. Medical procedures like palatoplasty, commonly utilized to address anatomical irregularities, can inadvertently lead to upper airway obstruction. Additionally, various risk factors influence OSAS in children with CLP, making it a multifactorial condition. The ability to identify OSAS in children with CLP is essential because if left untreated it can cause cognitive deficits, behavioral problems, impaired growth, and cardiovascular complications. To minimize the underdiagnosis of OSAS, the related risk factors related to OSAS in children with CLP should be considered. This review article aims to investigate those risk factors in children with repaired CLP to enable early detection, which can prevent unexpected complications through proper interventions.